2: How to check the fuel level on the engine of your diesel-powered maize shelling machine - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
A practical guide on how a farmer can check the fuel level on the engine. Without the fuel the machine wouldn't operate. This video was developed with funding from USAID through the Africa RISING Ghana project which is led by the International Institute of Tropical Agriculture (IITA). The purpose of the video is not to instantly turn farmers into specialist technicians, but to empower them to be able to perform basic maintenance activities when they don't have access to technicians.